The Field Metabolic Rate, Water Turnover, and Feeding and Drinking Behavior of a Small Avian Desert Granivore During a Summer Heatwave - Cooper, Christine Elizabeth; Withers, Philip Carew; Hurley, Laura Leilani; Griffith, Simon Charles (Frontiers in Physiology, 2019)
Global environmental change is leading to an increase in the frequency, intensity and duration of extreme weather events, so effective environmental management requires an understanding not only of the physiological response of organisms to increased mean temperatures, but also to extreme environmental conditions. To determine the physiological consequences of heatwaves on energy and water balance of arid-adapted zebra finches (Taeniopygia guttata) we measured field metabolic rate and water turnover rate of wild, free-living finches during a heatwave (consecutive days of maximum Ta 40-45°C) and during a cooler period (maximum Ta 27°C) during a summer drought. To understand how birds accommodated their energy and water requirements, we also monitored feeding and drinking behaviour of zebra finches at the study site on hot and cold days over 2.5 months during the same summer. Zebra finches can accommodate heatwaves without major impacts on field energy or water turnover, even when the heatwave is superimposed on high summer temperatures and long-term drought, so long as drinking water is available. In fact, cooler periods may pose a greater energetic challenge than heat waves during drought, when food availability is limited, due to the increased thermoregulatory cost of maintaining a high Tb against a thermal gradient. Zebra finches avoided or limited activity during the most thermally challenging periods of the day. Their pre-emptive feeding and drinking in preparation for hours of relative inactivity at high Ta, together with a high body water content and reduced midday activity and metabolic heat production, enabled zebra finches to maintain body mass during a heatwave. Predicting upcoming periods of unfavourably high Ta, together with a high body water content, may be essential for survival by desert birds of extreme Ta during heatwaves.